Revolting families : toxic intimacy, private politics, and literary realisms in the German sixties - Smith, Carrie, 1975- (University of Toronto Press, 2013)
"Revolting Families thus extends the concept of negativity, which has long been part of post-war German philosophical and aesthetic theory, to the body in German literature and culture. Through an analysis of these texts and of contextual discourse, Smith-Prei develops a theoretical concept of corporeal negativity that works to provoke socio-political engagement with the private sphere."--Publisher description